Measuring happyiness and wellbeing in smart cities - Gomes, Joana Branco (2018)
Gomes, J. B., Rego, J. S., & Neto, M. D. C. (2018). Measuring happyiness and wellbeing in smart cities : lisbon case study. In SMARTGREENS 2018 - Proceedings of the 7th International Conference on Smart Cities and Green ICT Systems (Vol. 2018-March, pp. 270-277). SciTePress. ISBN 978-989-758-292-9. DOI: 10.5220/0006771102700277